Pengaruh Kemampuan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan - Annisa Rahma Fathiah; Johan Hursepuny; Sita Dewi (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2022)
This research determine the influence of work ability and work motivation on employee performance at the Ammara Beauty Clinic. This type of research is quantitative research because this research is analyzing. The data collection techniques used descriptive and explanative method. Quantitative data is a research procedure that produces numerical data and is generally analyzed using descriptive or inferential statistics. Furthermore, data collection techniques were carried out with saturated samples, by conducting direct research to agencies to obtain primary data, namely regarding work ability and work motivation at Ammara Beauty Clinic by distributing questionnaires to Ammara Beauty Clinic employees. As partially ,the results showed that Job Ability (X1) had an effect on Employee Performance (Y), Work Motivation (X2) affects Employee Performance (Y), .Meanwhile, WorkAbility (X1) and Work Motivation (X2) simultaneously affect employee performance (Y).